Design of The “Merdeka Belajar” Program for Students of High School Education - Choiron Firmansyah; Ubaidillah Ubaidillah; Busriyanti Busriyanti (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
Merdeka Belajar Program is a policy that aims to encourage students to master various competencies and knowledge that are important and useful when entering the world of work. This article reveals the Design Of The “Freedom to Learn” Program For Students Of High School Of Education Miftahul Midad Lumajang. In this type of qualitative research with a case study approach, the data is obtained from interviews, observation, and documentation then analyzed with the condensation stage, data display, and conclusion. The research findings show that based on the results of the study, it can be concluded that several programs implemented at Madrasah Ibtidaiyah 01 Candipuro are active literacy and numeracy programs for low-grade students, active programs visiting the library, entering class programs, extracurricular programs, exam success programs, helping adaptation technology using laptops or Android, assisting in the preparation of e-reports, as well as other administration needed by the school. Some designed programs can be implemented correctly according to the targeted objectives.